2019
DOI: 10.1007/s10973-019-08160-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of gases released under incomplete combustion using PCFC–FTIR

Abstract: In order to get new insights on cable behavior during real-scale fires, the gases released under incomplete combustion in pyrolysis combustion flow calorimeter were recorded for several PVC and halogen-free flame-retardant cables. Incomplete combustion was monitored by changing combustion temperature between 600 and 900°C. Gases were identified using PCFC-FTIR coupling. Quantitative assessment of different gases produced during combustion was also carried out. It appears that larger amounts of unburnt gases ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The T c,ig evaluation for the target type composed with the PVC cables (526 ± 21°C, Table 7) falls in the 500‐600°C range provided by Gong et al 15 that studied spontaneous ignition of similar cable type (ie, PVC external sheath and cross‐linked polyethylene [XLPE] insulation). Furthermore, the piloted ignition temperature was measured at around 300°C 16 for electric cables with a PVC external sheath. Accordingly, these outcomes confirm that the target type composed with the PVC cables spontaneously ignited.…”
Section: Resultsmentioning
confidence: 99%
“…The T c,ig evaluation for the target type composed with the PVC cables (526 ± 21°C, Table 7) falls in the 500‐600°C range provided by Gong et al 15 that studied spontaneous ignition of similar cable type (ie, PVC external sheath and cross‐linked polyethylene [XLPE] insulation). Furthermore, the piloted ignition temperature was measured at around 300°C 16 for electric cables with a PVC external sheath. Accordingly, these outcomes confirm that the target type composed with the PVC cables spontaneously ignited.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the composition of the sheaths is different even if the same decomposition steps can be found. Relying on our previous paper [21], three decomposition steps can be identified in the range 250°C to 320°C, 400°C to 460°C and 700°C to 760°C but their intensity depends on the material. The first step can be assigned to the dechlorination of PVC as well as the decomposition/volatilization of the plasticizer.…”
Section: Thermogravimetric Analysis Of Cable Sheathsmentioning
confidence: 79%
“…The temperature of the third step (if any) corresponds to the decomposition of a mineral additive as calcium carbonate. In a previous article, we have shown that calcium carbonate is present in sheath from cable A14 but it reacts at much lower temperature with PVC to form CaCl 2 [21]. Therefore, we assume that calcium carbonate should be present in higher amount in sheaths from cables C16 and D28 and a fraction of unreacted calcium carbonate decomposes at around 750°C.…”
Section: Thermogravimetric Analysis Of Cable Sheathsmentioning
confidence: 90%
See 2 more Smart Citations